The long noncoding RNA sONE represses triple‐negative breast cancer aggressiveness through inducing the expression of miR‐34a, miR‐15a, miR‐16, and let‐7a. Issue 11 (9th April 2019) - Youness, Rana A.; Hafez, Hafez M.; Khallaf, Emad; Assal, Reem A.; Abdel Motaal, Amira; Gad, Mohamed Z.
Abstract: Triple‐negative breast cancer (TNBC) represents an aggressive breast cancer subtype. Among young females, TNBC is the leading cause of cancer‐related mortalities. Recently, long noncoding RNAs (lncRNAs) are representing a promising pool of regulators for tuning the aggressiveness of several solid malignancies. However, this still needs further investigations in TNBC. The main aim of this study is to unravel the expression pattern of sONE lncRNA and its mechanistic role in TNBC. Results showed that sONE is restrictedly expressed in TNBC patients; its expression level is inversely correlated with the aggressiveness of the disease. sONE acts as a posttranscriptional regulator to endothelial nitric oxide synthase (eNOS) and thus affecting eNOS‐induced nitric oxide (NO) production from TNBC cells measured by Greiss reagent. Mechanistically, sONE is a potential tumor suppressor lncRNA in TNBC cells; repressing cellular viability, proliferation, colony‐forming ability, migration, and invasion capacities of MDA‐MB‐231. Furthermore, sONE effects were found to be extended to affect the maestro tumor suppressor TP53 and the oncogenic transcription factor c‐Myc. Knocking down of sONE resulted in a marked decrease in TP53 and increase in c‐Myc and consequently altering the expression status of their downstream tumor suppressor microRNAs (miRNAs) such as miR‐34a, miR‐15, miR‐16, and let‐7a. In conclusion, this study highlights sONE as a downregulated tumor suppressor lncRNA in TNBC cells acting through repressing eNOS‐induced NO production, affecting TP53 and c‐Myc proteins levels and finally altering the levels of a panel of tumor suppressor miRNAs downstream TP53/c‐Myc proteins. Abstract : sONE is a novel tumor suppressor long noncoding RNA (lncRNA) in triple‐negative breast cancer (TNBC). sONE lncRNA is restrictively expressed in TNBC patients. sONE expression level is inversely correlated with the aggressiveness of the disease. sONE expression level is almost diminished in young TNBC patients.